Effect of Lactobacillus casei 431 and Lactobacillus acidophilus La-5 on the physico-chemical property, sensory quality and volatile compounds in fresh Libyan white cheese - Dabaj, Fatma Khalifa Hussein (2021)
The development of new or improved fermented products is significantly stimulated due to the increasing demand for tasty and healthy foods. Libyan soft white cheese is a very popular traditional dairy product in Libya which is made from fresh or pasteurized milk. There is currently no documented research on the manufacture of fresh Libyan white cheese using Lactic acid bacteria. Thus, the present study is to develop a white cheese using the traditional Libyan manufacturing procedure as well as using Lactobacillus spp. Two cultures of lactobacilli (L. acidophilus La-5 and L. casei 431) were evaluated for their proteolytic activity using spectrophotometric assay, and the volatile organic compounds (VOCs) were specified by using headspace solid-phase microextraction coupled to gas chromatography (HS-SPME-GC) on milk fermentation to select the best strain. Both strains were able to exhibit extracellular proteolytic activities in a broad pH range in a liquid medium. L. casei 431 had high extracellular proteolytic activity in an acidic environment (10.50 and 3.31 U/mg in MRS media and whole cow milk, respectively). According to the findings of this study, the analysis of the VOCs produced during the milk fermentation with L. casei 431 and L. acidophilus La-5 led to the identification of a wide range of VOCs. L. casei 431 was able to create more common flavour compounds than L. acidophilus La-5, including 2,3-butanedione, 2-heptanone, 3-hydroxy-2-butanone, and 2-nonanone. The white cheese was made by adding L. casei 431 in the milk and curd. In this study the physico-chemical, microbial, texture parameters, volatile composition and sensory qualities and the effects of cold storage (5 C) on the characteristics of white cheese with the different inoculating stage of starter cultures were evaluated. The white cheese samples made with L. casei 431 kept the microbial quality during storage study. The L. casei 431 resulted in lower springiness, gumminess and chewiness of the white cheese samples compared to the traditional white cheese. Diacetyl, acetoin, 2-heptanone, hexanoic acid and butanoic acid were shown to be major aroma-active components in Libyan white cheese. From flavour profile, the white cheeses were described as cooked, creamy, whey, diacetyl, moisty, sweet, and sour cheese flavour. In addition to that, L. casei 431 could be successfully used to improve the keeping quality of white cheese for 9 days at 5 C. In this study, the sensory profiles of different pizza cheeses produced with mozzarella cheese and different levels of white cheese were studied using Quantitative Descriptive Analysis (QDA). The appearance, texture and flavour were evaluated. Besides that, the influence of baking methods (microwave and oven) on pizza cheese was also investigated. The principal component analysis showed a good separation of pizza cheese samples. The regression coefficients of scaled and significance indications for sensory characteristics in the different pizza cheese samples showed that the pizza cheese made with 75% mozzarella cheese and 25% white cheese, and baked in the microwave had the best appearance, textural and flavour characteristics. In summary, adding white cheese in pizza cheese gave top sensory characteristics.